Palm Vein Recognition Based on Centerline - Ali , Yossra H.; Razuqi , Zahraa Naji (Iraqi Journal of Science, 2022)
The palm vein recognition is one of the biometric systems that use for identification and verification processes since each person have unique characteristics for the veins. In this paper we can improvement palm vein recognition system have been made. The system based on centerline extraction of veins, and employs the concept of Difference-of Gaussian (DoG) Function to construct features vector. The tests results on our database showed that the identification rate is 100 % with the minimum error rate was 0.333.